Association of a functional Indoleamine 2,3-dioxygenase 2 genotype with specific immune responses - Køllgaard, Tania (Landes Bioscience, 2012)
Two frequent single-nucleotide-polymorphisms (SNPs) are present in the indoleamine 2,3-dioxygenase 2 (IDO2) gene that influence its enzymatic activity. Thus, one SNP (R248W) is associated with a reduction in IDO2 catalytic activity, whereas the other SNP (Y359stop) generates a premature stop codon abolishing activity completely. In the present study, we describe the presence of a specific cellular immune response in the periphery which correlated with the functional status of the IDO2 protein. Hence, the induction of IDO2-specific T cells in peripheral blood requires the presence of a functional IDO2 protein and, consequently, is restricted to individuals that are not homozygous for the stop codon. Furthermore, we detected stronger T-cell responses in donors with the homozygous Y wild type at position 359 when compared with the heterozygous genotype. Interestingly, we found a higher number of immune responses against IDO2 in patients homozygous for the 248W giving reduction in IDO2 activity compared with the 248R. Hence, spontaneous immune responses against IDO2 seem to be correlated with reduced enzymatic activity of IDO2. The patient IDO2 genotype may well influence the outcome of IDO2-based anti-cancer vaccination.